Reduction of T Lymphoma Cells and Immunological Invigoration in a Patient Concurrently Affected by Melanoma and Sezary Syndrome Treated With Nivolumab - Narducci, Maria Grazia; Tosi, Anna; Frezzolini, Alessandra; Scala, Enrico; Passarelli, Francesca; Bonmassar, Laura; Monopoli, Alessandro; Accetturi, Maria Pina; Cantonetti, Maria; Antonini Cappellini, Gian Carlo; De Galitiis, Federica; Rosato, Antonio; et al. (Frontiers in Immunology, 2020)
Despite the recent availability of several new drugs in hemato-oncology, T-Cell Lymphomas are still incurable and PD-1 blockade could represent a therapeutic chance for selected patients affected by these malignancies, although further studies are required to understand the biological effects of anti-PD-1 mAbs on neoplastic T-cells and to identify biomarkers for predicting and/or monitoring patients' response to therapy. Sezary Syndrome (SS) represents a rare and aggressive variant of Cutaneous T Cell Lymphoma (CTCL) with a life expectancy of less than 5 years, characterized by the co-presence of neoplastic lymphocytes mainly in the blood, lymph-nodes and skin. In this study we analyzed longitudinal blood samples and lesional skin biopsies of a patient concurrently affected by Sezary syndrome (SS) and melanoma who underwent 22 nivolumab administrations. In blood, we observed a progressive reduction of SS cell number and a raise in the percentage of normal CD4+ and CD8+ T cells and NK cells over total leukocytes. Eight weeks from the start of nivolumab, these immune cell subsets showed an increase of Ki67 proliferation index that positively correlated with their PD-1 expression. Conversely, SS cells displayed a strong reduction of Ki67 positivity despite their high PD-1 expression. On skin biopsies we observed a marked reduction of SS cells which were no more detectable at the end of therapy. We also found an increase in the percentage of normal CD4+ T cells with a concomitant decrease of that of CD8+ T and CD4+CD8+ T-cells, two cell subsets that, however, acquired a cytotoxic phenotype In summary, our study demonstrated that nivolumab marked reduced SS tumor burden and invigorated immune responses in our patient. Our data also suggest, for the first time, that Ki67 expression in circulating neoplastic and immune cell subsets, as well as an enrichment in T cells with a cytotoxic phenotype in lesional skin could be valuable markers to assess early on treatment SS patients' response to PD-1 blockade, a therapeutic strategy under clinical investigation in CTCL (ClinicalTrials.gov NCT03385226, NCT04118868).